The uncertainty of revenue costings in the medium term - Owen Hutchison; Iyanoosh Reporter; Rita Scholl; Gillian Beer; Declan Trott; Wei Ying Soh (The Australian Government, The Treasury, 2019)
Modelling of the revenue and, as appropriate, distributional impacts of policy options - known as "costings" - is an important input to policy decision making and provides a valuable evidence base for public debate. There is significant interest in the medium-term financial impact of tax policy changes, in part because the financial impact of tax policies can be very different at maturity. Medium-term costings are associated with a greater level of uncertainty compared with the forward estimates, reflecting uncertainty in underlying economic parameters, and around the behavioural response and changing structure of the target population. This paper outlines the challenges of forecasting and communicating estimates of the revenue impact of policies over the medium term. The variety of policy costings that Treasury undertakes and the benefits and shortcomings of static and dynamic microsimulation approaches are discussed, with the paper concluding that medium term estimates need to be treated and communicated with care.
Keywords: 330